Making duck bone meal as a source of calcium using the sidrap protein hydrolysis technology from poultry-based conventional food processing waste - Nurul Qisti; Rukmelia Rukmelia; Zulfatun Najah; Elsa Windiastuti; Monalisa Ibrahim; Putri Nurul Hikmah (Jurnal Teknika, 2021)
This research is a study to improve duck bone meal characteristics with higher calcium and protein content. This study aims to determine the best conditions of modification processing of duck bone meal based on the chemical characteristics and the highest calcium content. The research method was modified by Putranto et al., including washing, bone boiling, damage, presto process, boiling process, extraction of NaOH base, washing, drying, and flouring. The research was used a completely randomized experimental design (CRD), consisting of 3 treatments and three replications, namely P1 (NaOH immersion for 2 hours), P2 (NaOH immersion for 3 hours), and P3 (NaOH immersion for 4 hours). The data analysis technique was quantitative and analytic using ANOVA with a significance level of 5% using the SPSS application to determine the effect of immersing NaOH various treatments on the chemical characteristics of duck bone meal. The analysis includes yield, proximate composition, and calcium. In addition, physical, organoleptic, and microbiological analyses were carried out. The best of manufacture of duck bone meal which produces the best characteristics was found in the 3 hours immersion treatment (P2) with an average ash content of 56.88%, the water content of 4.08%, fat content of 14.45%, protein content of 23.08%, crude fiber content of 0.29%, phosphorus content of 12.03% and calcium content of 9.86%. Penelitian ini merupakan penelitian lanjutan untuk memperbaiki karakteristik tepung tulang itik dengan kandungan kalsium dan protein yang tinggi. Penelitian ini bertujuan untuk menentukan kondisi terbaik pada modifikasi proses pembuatan tepung tulang itik berdasarkan karakteristik kimia dan kandungan kalsium tertinggi. Metode penelitian merupakan modifikasi dari metode yang dilakukan oleh Putranto, dkk, diantaranya pencucian, perebusan tulang, pembersihan, proses presto, proses perebusan, ekstraksi basa NaOH, pencucian, pengeringan dan penepungan. Rancangan percobaan yang dilakukan adalah Rancangan Percobaan Acak Lengkap (RAL), yang terdiri dari 3 perlakuan dan 3 ulangan yakni P1 (Perendaman NaOH selama 2 jam), P2 (Perendaman NaOH selama 3 jam) dan P3 (Perendaman NaOH 4 jam). Teknik analisis data yang digunakan adalah analisis kuantitatif dan analitik menggunakan ANOVA dengan taraf nyata 5% menggunakan aplikasi SPSS untuk mengetahui pengaruh perendaman NaOH berbagai perlakuan terhadap karakteristik kimia tepung tulang itik. Analisis yang dilakukan meliputi rendemen, komposisi proksimat dan kalsium. Selain itu dilakukan analisa fisik, organoleptik dan mikrobiologi. Proses produksi tepung tulang itik yang menghasilkan karakteristik terbaik terdapat pada perlakuan perendaman selama 3 jam (P2) dengan rata-rata kadar abu 56.88%, kadar air 4.08%, kadar lemak 14.45%, kadar protein 23.08%, kadar serat kasar 0.29%, kadar fosfor sebesar 12.03% dan kadar kalsium 9.86%.